2010
DOI: 10.1016/j.fertnstert.2010.07.693
|View full text |Cite
|
Sign up to set email alerts
|

HOXA10 expression is decreased in endometrium of women with adenomyosis

Abstract: HOXA10 gene expression is decreased in secretory phase endometrium of women with adenomyosis. Diminished expression of HOXA10 is a potential mechanism explaining decreased implantation observed in women with adenomyosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
1
30
0
2
Order By: Relevance
“…In some published clinical reports [7][8][9]11], adenomyosis had a detrimental effect on IVF outcome in terms of pregnancy or live birth rate, indicating impaired endometrial receptivity. In the study of Fischer et al [33], expression of the HOXA10 gene, an established marker of endometrial receptivity, was shown to be decreased in the secretory phase in the endometrium of women with adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some published clinical reports [7][8][9]11], adenomyosis had a detrimental effect on IVF outcome in terms of pregnancy or live birth rate, indicating impaired endometrial receptivity. In the study of Fischer et al [33], expression of the HOXA10 gene, an established marker of endometrial receptivity, was shown to be decreased in the secretory phase in the endometrium of women with adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Hoxa11 −/− mice showed a more severe phenotype than the Hoxa10 −/− mice . In humans, it also was reported that the expressions of Hoxa10 and Hoxa11 in the endometrium increased significantly in the mid‐luteal phase, when the uterus is receptive to embryo attachment, and that these expressions were significantly lower in infertile women …”
Section: Molecular Mechanisms Of Decidualizationmentioning
confidence: 92%
“…84 In humans, it also was reported that the expressions of Hoxa10 and Hoxa11 in the endometrium increased significantly in the mid-luteal phase, when the uterus is receptive to embryo attachment, 88,89 and that these expressions were significantly lower in infertile women. [89][90][91][92] The BMPs belong to the transforming growth factor-beta superfamily of growth modulators 93 and transcripts that correspond to several BMP family members are expressed in mouse uteri. 94,95 In all the expressed BMPs in the uteri, only BMP2 was induced in response to P4, with intense expression in the SCs surrounding the implanted embryo.…”
Section: Molecul Ar Mechanis Ms Of Decidualiz Ationmentioning
confidence: 99%
“…Moreover, in the review, the authors refer to several papers that attempt to justify a possible association between adenomyosis and a lower rate of implantation (Xiao et al, 2010;Fischer et al, 2011). Fisher et al suggested that a low expression of the HOXA10 gene could be a potential mechanism of impaired implantation.…”
Section: Letter Effect Of Adenomyosis On Implantationmentioning
confidence: 99%